Transnational judicial dialogue : the Federal Supreme Court of Brazil and the jurisprudence of the U.S. Supreme Court - CUNHA, Bruno Santos (2025)
Courts often cite foreign laws and precedents in their decisions. A substantial body of legal research, spanning various jurisdictions, evidences the increase in judicial dialogue between national, supranational and international courts. At first glance, these cross-references seem more logical when the involved legal systems share similarities that facilitate such exchanges. However, the central case studied in this thesis deviates from this pattern. Washington and Brasília, the United States and Brazil, are notably different, especially in their legal systems (common law v. civil law). Yet, evidence shows that the Federal Supreme Court of Brazil (STF) has increasingly referenced decisions from the U.S. Supreme Court (SCOTUS) in recent years. This thesis examines this trend, contrasting the debates within the U.S. Supreme Court - particularly the famous “Scalia v. Breyer” debate on the use of foreign sources in constitutional interpretation - with those in the Brazilian context. The study draws on comparative constitutional law literature to explore the globalization of constitutional law, the spread of constitutional values, and how constitutional principles cross national borders. Concepts like legal transplants, migration, borrowing, and judicial dialogue are analyzed to understand the interaction between the STF and SCOTUS. In this context, “judicial dialogue” refers to the exchange of precedents among courts and judges across different legal regimes. Based on an original analysis of three distinct datasets - the STF general docket (2000-2024), the Court’s Informativos, and Recursos Extraordinários with “general repercussion” between 2010 and 2024 - the thesis identifies patterns in 2.564 references to the U.S. Supreme Court found across 1.133 STF decisions. The patterns are based on each Justice’s legal background, the impact of judicial education on their approach to foreign law, and highlights the areas where the STF most frequently cites U.S. cases. The project aims to offer a detailed understanding of the factors driving the STF’s engagement with U.S. case law, suggesting directions for future research. It uncovers the complexities of judicial influence between the U.S. Supreme Court and the Federal Supreme Court of Brazil, contributing to the broader discourse on the globalization of constitutional law and the role of foreign precedents in national courts.